2016
DOI: 10.2337/dc16-1529
|View full text |Cite
|
Sign up to set email alerts
|

Urine Proteome Specific for Eye Damage Can Predict Kidney Damage in Patients With Type 2 Diabetes: A Case-Control and a 5.3-Year Prospective Cohort Study

Abstract: Urine haptoglobin, which is specific for PDR, is a novel biomarker and complement to urine albumin for predicting kidney damage in patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…In an interesting recent contribution, Yang et al . found urinary proteins specific for proliferative diabetic retinopathy in a cohort of 210 patients with type 2 diabetes.…”
Section: Urinary Proteomicsmentioning
confidence: 99%
“…In an interesting recent contribution, Yang et al . found urinary proteins specific for proliferative diabetic retinopathy in a cohort of 210 patients with type 2 diabetes.…”
Section: Urinary Proteomicsmentioning
confidence: 99%
“…Some studies have shown that the gene 677C/T polymorphism might be related to an increased risk of DN and DR. 15 Some scholars think that there are similar molecular pathways leading to damage to the diabetic kidney and retinal microvasculature, 16,17 and oxidative stress plays an important role in this process. 18 This study aims to build a convenient and practical prediction model to evaluate the risk of DN or DR in T2DM patients. At present, most literature related to T2DM is related to factors of DN or DR. To avoid neglecting the potential relationship between DN and DR and improve the reliability of the results, this study first screened the risk factors for DN and DR, and patients with both DN and DR were further tested.…”
Section: Introductionmentioning
confidence: 99%
“…A 5.3-year prospective cohort study, performed by Yang' group [24], found that the risk of renal insufficiency is higher if the baseline urinary Hp is equal or larger than 20 ng/min in T2DM patients. However, previous studies [11,22,24] didn't investigate the relationship between urine Hp and renal tubular damage. Hence, we further confirmed the correlation between UHCR and tubular injury biomarkers.…”
Section: Discussionmentioning
confidence: 99%